The Effect of Early Marriage Education on the Level of Knowledge of Adolescents about the Impact of Early Marriage - Ririnisahawaitun; Maruli Taufandas; Hariawan Junardi; Anatun Aupia (Caring: Indonesian Journal of Nursing Science, 2023)
Marriage is a sacred bond between man and woman to be husband and wife to form a happy and eternal family by believing in the one and only God. Early marriage can lead to high maternal and infant mortality, miscarriage, congenital disabilities in babies, and low birth weight. One of the efforts to reduce early marriage is to increase adolescent knowledge about early marriage by educating them on the impact of it. This study aims to determine the effect of early marriage education on the adolescent level on the impact of early marriage. This study is pre-experiment using a one-group pretest post-test design. The study population is 62 students in XI grade SMKN 1 Pringgasela, East Lombok Regency. All respondents were grouped, educated on early marriage, and presented orally using Powerpoint for 30 minutes. Their knowledge level on the impact of early marriage before and after the education was measured using a questionnaire consisting of 32 questions that had been tested for validity and reliability. The results showed an increase in their knowledge level with a mean pretest of 15.10 and a mean posttest of 31.90 (delta mean = 16.80). Based on the Wilcoxon test, the study obtained p = 0.000. It can be concluded that providing early marriage education impacts students' knowledge level at SMKN 1 Pringgasela, East Lombok Regency, with a p-value < 0.05. It is expected that the school will continue providing early marriage education regularly to reduce the occurrence of early marriage.